Biogeochemical implications of the ubiquitous colonization of marine habitats and redox gradients by Marinobacter species - Handley, Kim M.; Lloyd, Jonathan R. (Frontiers in Microbiology, 2013)
The Marinobacter genus comprises widespread marine bacteria, found in localities as diverse as the deep ocean, coastal seawater and sediment, hydrothermal settings, oceanic basalt, sea-ice, sand, solar salterns, and oil fields. Terrestrial sources include saline soil and wine-barrel-decalcification wastewater. The genus was designated in 1992 for the Gram-negative, hydrocarbon-degrading bacterium Marinobacter hydrocarbonoclasticus. Since then, a further 31 type strains have been designated. Nonetheless, the metabolic range of many Marinobacter species remains largely unexplored. Most species have been classified as aerobic heterotrophs, and assessed for limited anaerobic pathways (fermentation or nitrate reduction), whereas studies of low-temperature hydrothermal sediments, basalt at oceanic spreading centers, and phytoplankton have identified species that possess a respiratory repertoire with significant biogeochemical implications. Notable physiological traits include nitrate-dependent Fe(II)-oxidation, arsenic and fumarate redox cycling, and Mn(II) oxidation. There is also evidence for Fe(III) reduction, and metal(loid) resistance. Considering the ubiquity and metabolic capabilities of the genus, Marinobacter species may perform an important and underestimated role in the biogeochemical cycling of organics and metals in varied marine habitats, and spanning aerobic-to-anoxic redox gradients.